Investigating factors enhancing customer satisfaction towards The Store (Soon Seng Plaza) Melaka / Barbara Wilfred and Nur Farahin Fauzi - Wilfred, Barbara; Fauzi, Nur Farahin (Faculty of Business and Management, 2014)
The purpose of this study is to investigate the factors that can enhance customer satisfaction toward The Store. The objectives of this research study are to determine the most influential factors affecting customer satisfaction and the most significant of the factors that is organization, merchandise, facilities and price affecting customer satisfaction towards The Store. This research has been conducted based on a sample size of 100 respondents and using non-probability sampling technique. The results showed that the factors involved such as organization, merchandise, facilities and price have significant relationship with customer satisfaction. To analyses the data the researcher adopts Scientific Program of Social Science (SPSS) application. Findings are interpreted using reliability, frequency, correlation and regression. The conclusion and recommendation has been done for future study towards The Store.